A Genetic Algorithm for Regression Test Case Prioritization - Saklani, Neeraj Kumar; Singh, Parulpreet (International Journal of Computer Sciences and Engineering, 2025)
Regression testing is used to retest the modified version of software. Regression testing is expensive but still an important process. In regression testing, test case prioritization is used to improve the efficiency of the regression test suite by executing the most critical test cases first. As retesting of entire program is not possible with adequate time and cost i.e. only subset of all test cases will execute for regression testing. In this paper, we introduce a technique for regression test case prioritization based on supervised machine learning. We use Genetic Algorithm to make test case description processable for machine learning. In our approach we have consider machine learning classification model logistic regression to evaluate and calculate the prioritization quality. Our result indicates that our technique gives more accurate result as compare to other techniques. We use hybrid combination of genetic algorithm and logistic regression to improve the test case prioritization technique.